GEJALA PENYERTA PADA BALITA DIARE DENGAN INFEKSI ENTEROPATHOGENIC Escherichia coli (EPEC) DI PUSKESMAS RAWAT INAP KOTA PEKANBARU - Citra Ayu Anggreli; Dewi Anggraini; Maya Savira (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTEnteropathogenic Escherichia coli (EPEC) is a major cause of diarrhea in children below 5 years of age in the developing countries. The present study to detect the symptoms EPEC from childhood diarrhea has been done on April 2014 until October 2014. A total of 47 fecal specimens were collected from five hospitality primary health care in Pekanbaru and examination has been done in Microbiology Laboratory of Medical Faculty Riau University. The clinical manifestations are obtained is fever (57.45%), vomiting (46.80%), mucoid stools (36.17%), no symptoms (17.20%) and mild-moderate dehydration (74.46%). Results found that from all of the fecal specimen, 2 (4.35%) samples were positive EPEC. The infants with diarrhea who had positive EPEC experiencing fever and moderate dehydration.Keywords : Diarrhea, infants, hospitality primary health care, Enteropathogenic Escherichia coli